Constructed wetlands with Cyperus alternifolius as a sustainable solution for household greywater treatment. Issue 1 (1st July 2022) - Qomariyah, S; Utomo, B; Wahyudi, A H
Abstract: Compared to the conventional wastewater treatment plants, constructed wetlands (CWs) are low-cost and affordable green technologies for treating many types of wastewater. This study aimed to evaluate the sustainability of an old-single CW, after four years of operation, and compare its performance with a new-smaller CW, using Cyperus alternifolius plant and applying Hydraulic Retention Time (HRT) for one day. Two artificial wetlands, namely CW-B and CW-S, were used with dimensions (length x width x height) of 170 x 70 x 70cm and 71 x 42.5 x 52.5cm, respectively. The first operation of the CW-B was in September 2015 and the CW-S was in April 2019. Several concentrations of household greywater influent were loaded into the CWs to analyze their performance. Two aeration pipes were installed in the wetland system to increase the oxygen level in the systems. Water quality parameters namely Biological Oxygen Demand (BOD), Total Suspended Solid (TSS), detergent, and Dissolved Oxygen (DO) were laboratory tested before and after treatment. Research carried out during April to October 2019 resulted in the mean removal efficiencies for CW-B and CW-S being 94.13% and 96.84% for BOD; 95.04% and 95.62% for TSS; 97.11% and 94.61% for detergent; and 99.5% and 79.7% for DO increase, respectively. These findings indicate that the removal efficiencies of those parameters in both wetlands were not significantly different. Hence, the system of the old CW-B wetland still keeps a good working process. Referring to the national standards of water quality, the greywater effluents were safely discharged into water bodies and could be used for irrigation needs. A further study needs to be developed to maximize the detergent removal to meet the existing standard for hygiene sanitation. These results suggest that CWs are becoming a sustainable solution for the treatment of greywater at the household level and finally contributing to minimizing the pollution of water.